Hizmet means service : perspectives on an alternative path within Islam - Marty, Martin E., 1928- (University of California Press, 2015)
"Hizmet Means Service is an examination of the Hizmet movement. Hizmet is named for its focus on service, but it is also often called the Gulen movement, after the Turkish intellectual and inspiration for the movement, Fethullah Gulen, who is known for his contribution to improved interfaith relations. This book studies Hizmet in twelve chapters written by contributors from around the world. This book does not presume that all readers are familiar with Hizmet, but we move beyond mere introductions into scholarly analysis of Fethullah Gulen and the manifestations of this movement"--Provided by publisher.